2013
DOI: 10.1007/s12663-013-0508-5
|View full text |Cite
|
Sign up to set email alerts
|

The Recycling of Autoclaved Autografts in Mandibular Reconstruction: Case Report and Review of Literature

Abstract: Removal of pathological lesions from the mandible can leave a disfiguring appearance in addition to compromising the function of speech and mastication. It therefore becomes imperative to replace the lost part with bone grafts. Autogenous bone grafts-vascularised and non-vascularised, have been in vogue for the same. The probability of using the same resected bone after removal of all pathology has been done for a long time with mixed results in terms of uptake and viability. This paper presents a case of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Indeed, autoclaving is a key and puzzling point for the mechanisms underlying the osteoformation capacity of the PDBM paste observed in the present study. Autoclaved autografts or allografts have been used to reconstruct bone with interesting results [37,38] while it has been reported that in addition to the denaturation of bone organic matrix, autoclaving also alters its mechanical and structural properties [39,40]. Consequently, in the present study autoclaving the PDBP, in addition to transforming the outer demineralized organic phase in a collagen-rich gelatin probably modifies the structural and biomechanical properties of the mineral part preserved in the core, thereby influencing the cell behavior in a multifacet manner.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, autoclaving is a key and puzzling point for the mechanisms underlying the osteoformation capacity of the PDBM paste observed in the present study. Autoclaved autografts or allografts have been used to reconstruct bone with interesting results [37,38] while it has been reported that in addition to the denaturation of bone organic matrix, autoclaving also alters its mechanical and structural properties [39,40]. Consequently, in the present study autoclaving the PDBP, in addition to transforming the outer demineralized organic phase in a collagen-rich gelatin probably modifies the structural and biomechanical properties of the mineral part preserved in the core, thereby influencing the cell behavior in a multifacet manner.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the method used, the process of sterilization effectively kills all living cells, including those that orchestrate bone healing and viability, and the osseous segment acts only as scaffolding for bone ingrowth from the periphery. 5,6,11 The long-term outcomes of these reconstructive efforts remain unknown.…”
Section: Discussionmentioning
confidence: 99%